Misdiagnosed large bladder stone after laparoscopic radical prostatectomy and literature review: a case report - Gao, Wenbo; Xu, Yangkai (Frontiers in Oncology, 2025)
Large bladder stone is an uncommon disease, and its diagnosis is sometimes challenging. Herein we reported the case of a 75-year-old male patient who was admitted to undergo open cystostomy for a diagnosis of “urinary incontinence, urethral stricture, post-radical prostatectomy state, and urinary tract infection”. However, during the operation, we found that he was misdiagnosed by preoperative MRI examination, and he had a large bladder stone measuring approximately 6 × 5 cm and weighing 105 grams. Furthermore, the stone was found to be caused by a migrated Hem-o-lok clip originating from the previous laparoscopic radical prostatectomy. The eventual treatment is open cystolithotomy. Postoperatively, careful re-interpretation of the MRI film revealed a stone in the bladder, but the large stone was missed preoperatively. Doctors should be aware of the characteristics of bladder stone on MRI examination, and the diagnosis of bladder stones formed by foreign bodies requires a combination of multiple imaging methods to be confirmed.